How to complement traditional instruments to measure the economic dimension of food security in older people? An application for regions of Argentina - Milva Geri; Gisela González
Introduction: One of the dimensions of food security has to do with economic access to food. Aim: Propose a methodology that allows evaluating economic access to food in Argentina for the elderly population. Methods: Dietary guides for the Argentine population are used. Meanwhile, the food consumption patterns observed in the elderly population in Argentina are considered from a household expenditure survey, from which implicit food prices can also be obtained. Results: Six dietary plans corresponding to different regions of the country are designed and evaluated and it is found that they would be affordable only in two of the six regions analyzed. Conclusion: in the Metropolitan, Pampas, Cuyo, and Northeast regions the cost of the ideal basket is higher than food spending, fundamentally in the Northeast region where food spending should increase by 25%.